Limitations of the Principle of Immediacy in the Polish Criminal Procedure - Orłowska-Zielińska, Bogna; Szczechowicz, Krystyna (Studia Warmińskie, 2014)
The article discusses the principle of immediacy and its function in the Polish criminal procedure. In spite of the fact that the principle in question was not defined in the Code of Criminal Procedure of 1997 that is currently in force, its validity in the current legal status is unquestionable. The principle of immediacy includes three narrower directives which are strictly correlated. The objective of the following article was to present the complex nature of this principle and conduct the analysis of limitations that the principle is subject to.